Roles of Fructosyltransferase and Levanase-Sucrase of Actinomyces naeslundii in Fructan and Sucrose Metabolism - Bergeron, Lori J. (American Society for Microbiology, 2001)
The ability of Actinomyces naeslundii to convert sucrose to extracellular homopolymers of fructose and to catabolize these types of polymers is suspected to be a virulence trait that contributes to the initiation and progression of dental caries and periodontal diseases. Previously, we reported on the isolation and characterization of the gene, ftf, encoding the fructosyltransferase (FTF) of A. naeslundii WVU45. Allelic exchange mutagenesis was used to inactivate ftf, revealing that FTF-deficient stains were completely devoid of the capacity to produce levan-type (β2,6-linked) polysaccharides. A polyclonal antibody was raised to a histidine-tagged, purified A. naeslundii FTF, and the antibody was used to localize the enzyme in the supernatant fluid. A sensitive technique was developed to detect levan formation by proteins that had been separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and the method was used to confirm that the levan-synthesizing activity of A. naeslundii existed predominantly in a cell-free form, that a small amount of the activity was cell associated, and that the ftf mutant was unable to produce levans. By using the nucleotide sequence of the levanase gene of a genospecies 2 A. naeslundii, formerly Actinomyces viscosus, a portion of a homologue of this gene (levJ) was amplified by PCR and inserted into a suicide vector, and the resulting construct was used to inactivate the levJ gene in the genospecies 1 strain WVU45. A variety of physiologic and biochemical studies were performed on the wild-type and LevJ-deficient strains to demonstrate that (i) this enzyme was the dominant levanase and sucrase of A. naeslundii; (ii) that LevJ was inducible by growth in sucrose; (iii) that the LevJ activity was found predominantly (>90%) in a cell-associated form; and (iv) that there was a second, fructose-inducible fructan hydrolase activity produced by these strains. The data provide the first detailed molecular analysis of fructan production and catabolism in this abundant and important oral bacterium.